Results of quantitative chest-CT in chronic pulmonary graftvs.- host disease (cGvHD) 3 years after allogeneic stem cell transplantation - Kloth, Christopher; Thaiss, Wolfgang M.; Hetzel, Jürgen; Bier, Georg; Wirths, Stefan; Nikolaou, Konstantin; Horger, Marius (Journal of Thoracic Disease, 2017)
Background: To quantify lung parenchymal changes in symptomatic patients with chronic pulmonary graft-versus-host disease 3 years after allogeneic stem cell transplantation (allo-SCT) by means of CT-densitometry (CTD) and to compare results with those of established pulmonary function tests (PFT). Methods: The study group consisted of 26 patients with pulmonary cGvHD (19 males, 7 females; mean age, 49.29±15.89; range, 19–72 years). The diagnosis was based on clinical symptoms, PFT and chest-CT findings. CTD and PFT were performed both in the pre- and post-transplantation setting and results compared with each other. CT scans were obtained during suspended deep inspiration including the whole lungs. The mean lung attenuation (MLD), low attenuation values (LAV) and distribution of focal parenchymal abnormalities compatible with emphysema (HU